Measuring sleep quality in older adults: a comparison using subjective and objective methods - Landry, Glenn J.; Best, John R.; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2015)
Sleep quality decreases with aging and thus sleep complaints are prevalent in older adults, particularly for those with cognitive impairment and dementia. For older adults, emerging evidence suggests poor sleep quality increases risk of developing cognitive impairment and dementia. Given the aging population – and the impending economic burden associated with increasing numbers of dementia patients – there is pressing need to improve sleep quality among older adults. As such, research efforts have increased focus on investigating the association between age-related sleep changes and cognitive decline in older adults. Sleep quality is a complex construct to evaluate empirically, and yet the Pittsburg Sleep Quality Index (PSQI) is commonly used in studies as their only measure of sleep quality. Furthermore, the PSQI may not be the best sleep quality measure for older adults, due to its reliance on the cognitive capacity to reflect on the past month. Further study is needed to determine the PSQI’s validity among older adults. Thus, the current study examined sleep quality for 78 community dwelling adults 55+ to determine the PSQI’s predictive validity for objective sleep quality (as measured by actigraphy). We compared two subjective measures of sleep quality – the PSQI and Consensus Sleep Diary (CSD) – with actigraphy (MotionWatch 8; camntech). Our results suggest perceived sleep quality is quite different from objective reality, at least for adults 55+. Importantly, we show this difference is unrelated to age, gender, education, or cognitive status (assessed using standard screens). Previous studies have shown the PSQI to be a valuable tool for assessing subjective sleep quality; however, our findings indicate for older adults the PSQI should not be used as a substitute for actigraphy, or vice versa. Hence, we conclude best practice is to include both subjective and objective measures when examining sleep quality in older adults (i.e., the PSQI, CSD, and actigraphy).